Analysis of Students’ Mathematical Problem-Solving Abilities in Single Variable Linear Equations and Pythagorean Theorem Material - Meida Rosita; Iyan Rosita Dewi Nur; Kiki Nia Sania Effendi (PRISMA, 2026)
This study aims to analyze students' mathematical problem-solving abilities in Single Variable Linear Equations and the Pythagorean Theorem based on Polya's problem-solving stages. The study uses a descriptive qualitative approach involving 40 eighth-grade students VIII junior high school students through descriptive tests and interviews. The results of the analysis show that students' mathematical problem-solving abilities are in the moderate category for both subjects, with an average score of 74.85 for Single Variable Linear Equations and 74.67 for the Pythagorean Theorem. Students in the high category are able to go through all stages of problem solving systematically. Students in the moderate category were able to understand the problem and plan a solution strategy, but often made computational errors. Conversely, students in the low category had difficulty understanding information, constructing mathematical models, and implementing solution procedures. Overall, the results of this study confirm the need to strengthen problem-solving-based learning that emphasizes understanding concepts and solution strategies to optimally improve students' mathematical problem-solving abilities.